(untitled) (Journal of Scientific Research, 2022)
Graphene has attracted great attention to researchers nowadays for its electronic, optical, and mechanical properties. A key requirement for applications is the development of industrial-scale, reliable, and inexpensive production processes. In this work, we present a scalable approach of graphene synthesis from a biomass source such as hemp bat fiber which is called hemp bast fiber derived graphene (HGr). The structure and morphology of HGr are confirmed by performing several characterization techniques such as XRD, Raman spectroscopy, and TEM analysis. Mesoporosity of the HGr is confirmed by BET surface area and BJH pore size distribution analysis.